A Nuanced Look at Women in STEM Fields at Two-Year Colleges: Factors that Shape Female Students’ Transfer Intent - Wang, Xueli; Chan, Hsun-yu; Soffa, Sara Jimenez; Nachman, Brett Ranon (Frontiers in Psychology, 2017)
In this study, we explored the relationship between the intent to transfer upward and a set of motivational, contextual, and socio-demographic background factors among 696 female students beginning in science, technology, engineering, and mathematics (STEM) programs or courses at two-year colleges in a Midwestern state. Drawing upon survey data and administrative records, our multinomial logistic regression analysis revealed that students’ transfer intent is subject to potential influences of their math and science self-efficacy beliefs, as well as transfer-oriented interaction. In addition, the association between transfer intent and key motivational and contextual factors was moderated by students’ racial/ethnic backgrounds, marital status, and childcare obligations. These findings bear important and nuanced implications as policymakers, educators, and researchers continue to discover ways to better support women’s educational pathways and success in STEM fields at and through two-year colleges.